Adsorption-Desorption Studies on Cr(VI) Using Non-Living Fungal Biomass - Sen, Mousumi; Ghosh Dastidar, Manisha (Asian Journal of Chemistry, 2010)
The present study was undertaken in batch bioreactor with an aim to examine the Cr(VI) adsorption potential of the non-living fungal biomass of Aspergillus sp. from aqueous solution and also to find out the possibility of recovering of Cr(VI) from the metal concentrated fungal biomass. The optimum pH for adsorption of Cr(VI) was found to be 2.0. The Cr(VI) adsorbed increased with increasing initial metal concentration upto 500 mg L-1. A maximum removal of 27.5 mg g-1 was observed at pH 2.0 at 500 mg L-1 initial Cr(VI) concentration. The adsorption equilibrium constants were obtained from both Freundlich and Langmuir adsorption isotherms. Desorption studies carried out using a number of desorbing agents indicated a maximum of 76 % of Cr(VI) was recovered from the metal concentrated biomass using 0.1 N sodium hydroxide solution within 0.5 h of time period.